Detection of COVID-19 vaccine rejection situation and reasons in people over 18 years of age applying to family health centers in Karabük and its relationship with health literacy level - EKMEKCİ, Gülşah Büşra and Nacar, Erkay and Arıcan, Ali Ayberk (Scientific Reports in Medicine, 2025)
Abstract Objective: The aim of this study is to examine the rejection of the COVID-19 vaccine, its reasons and its relationship with health literacy levels. Material and Method: This study is a cross-sectional analytical study. The sample of the research consisted of 648 people who applied to family health centers in Karabük province between May 2022 and June 2022 and agreed to participate in the research. "Sociodemographic Characteristics", "Questions determining the characteristics of COVID-19 vaccine rejection" and "Health Literacy Scale TSOY-32 scale" were used to collect data. Descriptive characteristics of people are expressed with frequency and percentage in categorical data. Pearson Chi-Square and Fisher’s Exact Test were used. A value of p<0,05 was considered significant. Results: It is seen that 31.6% of the participants have an inadequate health literacy level, 36.9% have a problematic-limited health literacy level, 21.9% have an adequate health literacy level and 9.6% have an excellent health literacy level. A significant difference was found between rejection of the COVID-19 vaccine and health literacy (p = 0.014). Conclusion: As a result, by increasing the level of health literacy, positive attitudes towards the COVID-19 vaccine will also increase. It is thought that positive attitudes towards the COVID-19 vaccine will increase by increasing health literacy levels. Therefore, it seems that there is a need for research to increase health literacy Keywords : COVID19, COVID-19 vaccines, health literacy, vaccination refusal